PENGARUH KUALITAS PELAYANAN WEBSITE AKADEMIK TERHADAP MINAT KULIAH DI AKBP PADANG - Marlius, Doni; Ananda, Febryandhie (JURNAL PUNDI, 2019)
College interest is an attitude of interest, pleasure, love, students towards a learning activity or lecture at a particular tertiary institution or in a particular department. The purpose of this study was to determine the effect of academic website service quality on interest in studying at AKBP Padang. Using multiple linear regression analysis that serves to measure the influence between tangible variables, reliability, responsibility, assurance, and empathy for the interest in lectures at AKBP Padang, the number of samples that can be used in this study were 57 respondents, the sampling technique used in this research is through non probability sampling. The results showed tangible, reliability, responsibility, assurance, and empathy variables partially or jointly had a significant effect on interest in studying at Padang AKBP.